Analisis TCP Cubic dan Simulasi untuk Menentukan Parameter Congestion Window dan Throughput Optimal pada Jaringan Nirkabel Ad Hoc - Ary Firnanda; Teuku Yuliar Arif; Syahrial Syahrial (Universitas Syiah Kuala, 2017)
Ad hoc wireless network performance often declines caused the onset of congestion on the process of sending data. TCP Congestion Control used to solve these problems. TCP Cubic is one variant TCP Congestion Control. This research was conducted with the test and compare between variable value b=0.2 with the value of the variable b to be used in ad hoc wireless networks. This research was conducted with the experimental method using network simulation software NS-3. The results showed that the value of variable b is the right on ad hoc wireless network with packet loss by 5% to generate optimal congestion window max is b=0.5 and the average throughput optimal is b=0.1